2020
DOI: 10.1111/liv.14422
|View full text |Cite
|
Sign up to set email alerts
|

Low‐GGT intrahepatic cholestasis associated with biallelic USP53 variants: Clinical, histological and ultrastructural characterization

Abstract: Background & Aims:In about 20% of children with cholestasis and normal or low serum gamma-glutamyltransferase (GGT) activity, no aetiology is identified. We sought new genes implicated in paediatric hepatobiliary disease. Methods:We conducted whole-exome sequencing in 69 children evaluated at our centre from 2011 to 2018 who had low-GGT cholestasis and in whom homozygous/ compound heterozygous predictedly pathogenic variants (PPVs) in ATP8B1, ABCB11, NR1H4, MYO5B or TJP2 were not found. Clinical records and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 22 publications
(33 reference statements)
1
50
0
Order By: Relevance
“…Biallelic variants in USP53 have recently been reported in cholestasis phenotype. Up to now, a total of 29 cases from 22 families have been reported in 6 articles in the literature showing that the USP53 gene is associated with cholestasis and/or some additional phenotypes [5,7,[18][19][20][21]. Detailed clinical, laboratory, and genetic ndings of all cases reported in the literature and our own case (totally 30 cases) are summarized in Table-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biallelic variants in USP53 have recently been reported in cholestasis phenotype. Up to now, a total of 29 cases from 22 families have been reported in 6 articles in the literature showing that the USP53 gene is associated with cholestasis and/or some additional phenotypes [5,7,[18][19][20][21]. Detailed clinical, laboratory, and genetic ndings of all cases reported in the literature and our own case (totally 30 cases) are summarized in Table-2.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, studies have shown that USP53 co-locates with TJP2 and contributes to tight junction structures, at least in the ear [8]. Pathogenic variants detected in the TJP2 gene have been shown to be associated with hypercholanemia, normal or low GGT intrahepatic cholestasis, hepatocellular carcinoma as well as deafness [5,8,22]. However, we recommend that cases with variants in USP53 gene should be monitored for hearing loss and that aminoglycoside antibiotics should not be used in these patients because of the additional damage they may cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP53 fulfills important physiological functions in different tissues [ 87 , 88 , 89 , 90 , 91 ] and has been associated with cancer progression [ 92 , 93 , 94 ]. Kurban et al reported a duplication in the genomic locus of USP53 , MYOZ2 , and FABP2 in a patient with bone deformities and severe obesity (BMI > 40), later diagnosed with Cantu syndrome [ 89 ].…”
Section: Usps and Osteoblastsmentioning
confidence: 99%
“…TJP2 encodes the tight junctionassociated protein zona occludens (ZO)2, and its loss of function is believed to compromise the tight junction function leading to the paracellular leakage of bile [21,22]. The importance of tight junctions in securing normal bile flow is supported by the recent identification of pathogenic variants in USP53, encoding a member of the deubiquitinating enzyme family that colocalizes and interacts with ZO2 at tight junctions in epithelial cells [27], in a patient with idiopathic FIC [28]. NR1F4 encodes FXR, and pathogenic NR1F4 variants are associated with the loss of ABCB11 expression [23].…”
Section: An Introduction To the Enterohepatic Circulation Of Bile Acimentioning
confidence: 99%